Integration and effectiveness of the Philippine College of Arts and Trades - Vergara, Jose R. 1918-
This study was conducted to determine the extent of integration of the college departments and units in its mission of offering industrial-technical education program on a higher level in order to come up with a contingency model for application to similar institutions or for further study. Questionnaires were sent to 172 personnel, 942 students and 548 graduates of 1975-1976. Interviews were conducted with employers and industrial company officials who assist in the college program of on the job (in-plant) training and heads of schools cooperating in the student teaching program of the college. The overall mean integration was medium. The departments and programs are integrated in terms of goals, tasks, structure, communication, and decision-making and are therefore effective.